Avian Interferon-Inducible Transmembrane Protein Family Effectively Restricts Avian Tembusu Virus Infection - Chen, Shilong; Wang, Long; Chen, Jieying; Zhang, Lanlan; Wang, Song; Goraya, Mohsan U.; Chi, Xiaojuan; Na, Yang; Shao, Wenhan; Yang, Zhou; Zeng, Xiancheng; Chen, Shaoying; et al. (Frontiers in Microbiology, 2017)
Avian Tembusu virus (ATMUV) is a highly pathogenic flavivirus that causes significant economic losses to the Chinese poultry industry. Our previous experiments demonstrated that ATMUV infection effectively triggered host innate immune response through MDA5 and TLR3-dependent signaling pathways. However, little information is available on the role of interferon-stimulated genes (ISGs) in defending against ATMUV infection. In this study, we found that ATMUV infection induced robust expression of type I and type III interferon (IFNs) in duck tissues. Furthermore, we observed that expression of interferon-inducible transmembrane proteins (IFITMs) was significantly upregulated in DEF and DF-1 cells after infection with ATMUV. Similar results were obtained from in vivo studies using ATMUV-infected ducklings. Importantly, we showed that knockdown of endogenous IFITM1 or IFITM3 by specific shRNA markedly enhanced ATMUV replication in DF-1 cells. However, disruption of IFITM2 expression had no obvious effect on the ATMUV replication. In addition, overexpression of chicken or duck IFITM1 and IFITM3 in DF-1 cells impaired the replication of ATMUV. Taken together, these results reveal that induced expression of avian IFITM1 and IFITM3 in response to ATMUV infection can effectively restrict the virus replication, and suggest that increasing IFITM proteins in host may be a useful strategy for control of ATMUV infection.